PENGARUH STRATEGI GREEN MARKETING PADA BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI RUMAH DI PERUMAHAN PT. ASTA KARYA PEKANBARU - Marhadi '; Nursyamsi Ayu; Henni Noviasari (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The In fluence of Green Marketing Strategy In Marketing Mix Decisions AgainstConsumers In Buying House In Residential Of PT. Asta Karya Pekanbaru.This research aimed to analyse the effect of Green Marketing on marketing mixvariables consisting of product, price, location and promotion of the consumer’sdecision to buy a house in residential of PT. Asta Karya Pekanbaru.This research using propotional random sampling technique in making the samplewith the sample number 268. The method of analysis used in this study wasdescriptive quantitative method and multiple linear regression analysis with SPSSVersion 17.The results showed: (a) green marketing strategies of a product has positive influence on consumer decision to buy a house in a residential of PT. Asta KaryaPekanbaru. (b) green marketing strategies such as price positive in fluence onconsumer decision to buy a house in a residential of PT. Asta KaryaPekanbaru(c) green marketing strategies such as location of a positive in fluenceon consumer decision to buy a house in a residential of PT. Asta KaryaPekanbaru.(d)green marketing strategies such as the promotion of a positive influence on consumers decision to purchase a house in residential of PT. AstaKarya Pekanbaru (e)green marketing strategies together a positive influenceonconsumer’ decision to purchase/buy a house in Residential of PT. Asta KaryaPekanbaru.Kata Kunci : Green Marketing, MarketingMix (Product, Price, Location,Promotion) and the Purchasing Decision.